OPTIMASI KONDISI PURIFIKASI PARSIAL LIPASE Aspergillus niger 65I6 SOLID STATE FERMENTATION (SSF) PADA MEDIUM BUNGKIL JARAK SEBAGAI SUMBER BELAJAR PENGANTAR MIKROBIOLOGI - Nurikasari, Maulina (Bioedukasi Jurnal Pendidikan Biologi, 2012)
Extracellular lipase is an enzyme that catalyzes the hydrolysis reaction of triglycerides into free fatty acids and glycerol and synthesis reaction of esters. Lipase can be produced by microbes include bacteria, fungi and yeasts. Lipase by Aspergillus niger 65I6 produced in the medium of Jatropha cake using solid-state fermentation has a different character of the lipase produced by other microorganisms. The aims of this research were to determine the optimum condition partially purified lipase by Aspergillus niger 65I6. The methods of this research were conducted in 2 steps: (1) production of lipase, (2) partial purification using ion exchange chromatography, (3) SDS-PAGE. The results of this research showed that partial purification lipase by Aspergillus niger 65I6 using anion exchange chromatography esterification activity of 45.58 U/ml with specific activity of 421.97 U/mg adsorbed at pH 8 and 0.5 M NaCl elution. Partially purified lipase by Aspergillus niger 65I6 was 86.11% yield and purification factor 12,12 and a molecular mass of Lipase by Aspergillus niger at 19 kDa estimated by SDS-PAGE. Found of this research can be explained for the development study of microbiology concept and practical contribution about procedure research simple design. Students understand about technique and condition of partial purification.  Kata kunci:         Lipase, Aspergillus niger, Solid-State Fermentation, Purifikasi, SDS-PAGE